2009
DOI: 10.1111/j.1476-5381.2009.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the different adrenoceptor targets of nebivolol enantiomers in rat thoracic aorta

Abstract: Background and purpose: Nebivolol is a highly selective b1-adrenoceptor antagonist with b3-adrenoceptor agonist properties and is a racemate mixture of D-and L-enantiomers. However, the cellular mechanisms of the effects of each enantiomer are not yet clear and are a matter for debate. The aim of the present experiments was to determine the adrenoceptors involved in the vascular effects of D-and L-enantiomers of nebivolol in rat thoracic aorta. Experimental approach: Responses to nebivolol enantiomers were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…, Tran Quang et al . ). Thanks to its combined activity as β 1 ‐ARs antagonist and β 3 ‐ARs agonist, nebivolol is used in human clinical studies to evaluate the effects of β 3 ‐ARs activation.…”
Section: Comparative Pharmacologymentioning
confidence: 97%
“…, Tran Quang et al . ). Thanks to its combined activity as β 1 ‐ARs antagonist and β 3 ‐ARs agonist, nebivolol is used in human clinical studies to evaluate the effects of β 3 ‐ARs activation.…”
Section: Comparative Pharmacologymentioning
confidence: 97%
“…Stimulation of the beta 3 -AR and activation of endothelial nitric oxide synthase (eNOS) increases NO release after nebivolol treatment to cause peripheral vasodilatation and improved endothelial function (16,17). Nebivolol might also activate the beta 2 -AR (1820). …”
mentioning
confidence: 99%
“…Thus we aimed to characterize the dilator properties of nebivolol in isolated basilar arteries, in such conditions, in which the intraluminal pressure and extravascular environment were controlled. Based on previous studies [ 17 , 34 , 35 , 44 ] we have used nebivolol in a range of 10 −7 to 10 −4 M which is in accordance with a range of concentrations used by others. Our data show significant dilations of BA in response to concentration-dependent administration of nebivolol ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example Evangelista et al reported that antioxidant properties of nebivolol can increase the “surviving” level of NO by reducing its oxidative inactivation in human umbilical vein endothelial cells, and that beta-1/2/3 adrenoceptors may play role in the development of nebivolol-induced dilation [ 43 ]. Moreover, Georgescu et al showed nebivolol induces beta-2 adrenoceptor-mediated and Ca 2+ activated potassium channel induced hyperpolarization with the consequent relaxation in mice renal arteries [ 35 ], whereas, Tran-Quang et al has demonstrated nebivolol-induced specific, either beta-2 and beta-3 agonist or alpha-1 and beta-1 antagonist adrenoceptor-mediated relaxations in rat aortic rings [ 44 ]. It was also observed that nebivolol elicits the release of hyperpolarizing factor via activation of calcium activated potassium channels [ 34 ] that—in part—maintains vessel relaxation when eNOS (endothelial NO synthase) is inhibited [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation